Contribuição ao entendimento da dinâmica geomorfológica atual do tabuleiro de Feira de Santana-Ba - Souza, Jobabe Lira Lopes Leite (2015)
The Feira de Santana board is configured in a geomorphological unit formed from the deposition of sediment Barreiras (BRASIL, 1981). The area has different characteristics along its length, characterized as a transition morphoclimatic domains, which generates a high complexity with respect to the processes that operate in the geomorphological evolution of the unit. In this context, the work presented here aims to characterize the morphodynamic behavior of Feira de Santana tray (BA) from the morphoclimatic system analysis and the work of morfopedológicos processes linked to fluid dynamics. The results shown here, as well as contributing to understand the geomorphological evolution of the Board, may be used as a basis for further geomorphological research in the area and will also serve as a basis for future action planning. The study proposed here is founded on the systemic methodology. In this context, the analysis was performed morphoclimatic the system by building models representing the spatial activity of the weather elements (rainfall intensity and rain), and to generate models and interpretations of shapes and features expressed in the current top of the tray. Such analyzes, coupled with structural analysis of soil cover, held on the eastern edge of the northern sector of the board, were of great importance for the development of research. It was found that the different degrees of performance of the rainfall intensity and the difference in water availability from the board, ranging from an intensity of 240 and 500, moderately stable vulnerable, respectively; and rainfall, between 750 and nearly 2000 mm of rain, both turning in the southeast-northwest direction, conditioned the genesis of different forms in the top of the board area. It is possible to partition the same into 4 areas that are distinguished regarding the forms of vouchers, the tops and sides. The morfopedológica analysis of the edge of the board strand identified a genetic correlation between soil horizons, which allowed, together with the definition of lateral conversion systems, the development of toposequence. We identified 10 different pedological volumes, due to its characteristics, conditioned the formation of four distinct sectors of hydrological dynamics along the topossequence